Comparative analysis of zinc oxide and aluminium doped ZnO for GHz CMOS MEMS surface acoustic wave resonator - Md Ralib @ Md Raghib, Aliza 'Aini; Nordin, Anis Nurashikin (2013)
CMOS integration in RF MEMS have become dominant due to the growing demand of mobile and wireless communication system. Usage of off chip resonators is not efficient since it leads to large area and high interfacing loss. Integration of CMOS with SAW resonators is a possible solution to reduce the loss. In this work, a SAW resonator was developed using AZO/Al/Si layers in 0.18 μm CMOS technology. AZO was chosen as the piezoelectric layer to achieve high electromechanical coupling coefficient for good SAW performance. This paper highlights the comparative analysis of two different piezoelectric materials: pure Zinc Oxide (ZnO) and Aluminium doped Zinc Oxide (AZO) for GHz CMOS MEMS SAW resonator. S parameter measurements were performed for the fabricated designs to get the resonance frequencies and the electromechanical coupling coefficients were recalculated. The design and finite element modeling simulation was conducted using COMSOLTM to verify the performance of the resonator using both Al-doped ZnO and pure ZnO via the simulation results.